Prey use and productivity of ferruginous hawks in rural and exurban New Mexico. Issue 8 (4th August 2016) - Keeley, William H.; Bechard, Marc J.; Garber, Gail L.
ABSTRACT: Habitat loss from human development affects native wildlife populations, especially in the western United States where the human population is growing 2–3 times faster than any other part of the country. We analyzed regurgitated pellets, prey remains, and video to describe the diet of ferruginous hawks ( Buteo regalis ) nesting in rural and exurban grasslands in New Mexico, USA, to better understand the conservation needs of this species. Three mammals—Botta's pocket gopher ( Thomomys bottae ), Gunnison's prairie dog ( Cynomys gunnisoni ), and desert cottontail ( Sylvilagus audubonii )—comprised the majority of ferruginous hawk diet in percent biomass, whereas Botta's pocket gopher dominated diet in percent frequency. Hawks breeding in the exurban grassland (i.e., exurban hawks) consumed more Gunnison's prairie dogs, whereas hawks in the rural area (i.e., rural hawks) consumed more lagomorphs. From 1998–2005, and during the 2 years of our prey use study, exurban hawks delivered more biomass and prey items and experienced greater nesting success and productivity than rural hawks. The presence of prairie dogs, a colonial mammal whose occurrence theoretically reduces predatory search time, assisted in the maintenance of relatively high productivity levels for exurban hawks in our study. In 2004, the exurban grassland supported 5 times more prairie dog colonies than the rural area, but the number of exurban colonies decreased by 50% from 1999–2004. Extant prairie dog colonies and habitat supporting other medium‐sized mammals (e.g., Geomyidae) should be conserved to enable maintenance of ferruginous hawk populations in the western United States, particularly in anthropogenically altered areas. © 2016 The Wildlife Society.